Application of Constitutional Court Decision No.18/PUU-XVII/2019 concerning Fiduciary to the protection of Consumer Rights: Konstitusionalitas Eksekusi Jaminan Fidusia dalam Kerangka Perlindungan Hak Konsumen - Salvia, Merva Putri; Putri, Luh Putu Yeyen Karista (Constitutional Court of the Republic of Indonesia, Indonesia, 2024)
The arbitrariness of creditors in carrying out parate executions is very disturbing and causes material and immaterial losses for debtors, this is because there are inappropriate norms in a quo article in the form of the phrase that the strength of a fiduciary guarantee certificate is equal with a valid court decision. fixed law and the phrase breach of contract. This research aims to describe changes in the implementation of parate execution as regulated in Article 15 paragraph 2 and paragraph 3 of Law 42/1999 before and after the Constitutional Court Decision and the implications of the Constitutional Court decision for the current fiduciary concept. This research uses a type of normative juridical research. The research results show that Article 15 paragraphs 2 and 3 conflict with the 1945 Constitution, this is because the basic norms contained in this Article do not have a single interpretation so they can be misused by creditors against debtors. With the Constitutional Court’s decision regarding the material review of the a quo article, it provides a clear picture of the current fiduciary guarantee mechanism. In order to follow up on justice and equality between debtors and creditors, it is necessary for the government to play a role in regulating it more efficiently.